Hubungan Penggunaan Gadget dengan Risiko Masalah Perkembangan Psikososial pada Anak Prasekolah - Kadek Linda Veniawati; I Ketut Labir; N.L.K. Sulisnadewi (Jurnal Gema Keperawatan, 2022)
The use of technology in the current era of globalization is getting faster, one of the most widely used technologies is gadgets which are one of the media for communicating with the aim of facilitating human communication activities. However, along with the development of the era, the use of gadgets has become one of the basic human needs so that there are many negative impacts caused by using gadgets because they cannot use gadgets properly. One of the negative impacts caused by the use of gadgets is the risk of psychosocial development problems. The purpose of this study was to determine the relationship of the history of gadget use with the risk of psychosocial development problems in preschool children in Jagaraga Village. This research method is correlational which is quantitative. The subject approach model used is cross sectional. The sampling technique used in sampling is non-probability sampling with purposive sampling, namely 97 respondents. Collecting data using a questionnaire technique. Pearson's statistical test obtained a p on the intensity of gadget use with the risk of psychosocial development problems, which is 0.001, then Ho is rejected and Ha is accepted, meaning there is a significant or correlated relationship. this states that there is a relationship between a history of gadget use and the risk of psychosocial development problems in preschool children in Jagaraga Village, Buleleng Regency.